Prebiotic Potential and Value-Added Products Derived from Spirulina laxissima SV001—A Step towards Healthy Living - Vidya Sankarapandian; Kirubakaran Nitharsan; Kavitha Parangusadoss; Prakash Gangadaran; Prasanna Ramani; Balu Alagar Venmathi Maran; Manasi P. Jogalekar (MDPI, 2022)
Lately, microalgae-based value-added products have been gaining market value because they moderate the dependency on fossil fuel and high-value chemical products. To this end, the purpose of this study was to develop prebiotic products from the microalgae Spirulina sp. The microalgae were isolated from the fresh water and characterized at the molecular level. The dry biomass, chlorophyll content, phycocyanin, cytotoxicity and antimicrobial and antioxidant properties of the isolated strains were analyzed. Moreover, value-added products like Spirulina cake, chocolate, tea, vermicelli and Spirulina juice were made for a vulnerable population due to high nutritive value.